Scottish Gaelic political terminology – Term formation in the Scottish Parliament Annual Report - Lena Krochmann (LingBaW)
This paper analyses the Scottish Gaelic political terminology used by the Scottish Parliament, based on the translations of three Annual Reports. Applying principles from terminology theory and taking minority-language concerns into account, the Scottish Gaelic terms are examined for methods of term formation and their relation to their English and, where applicable, Irish equivalents. Inconsistencies in the terminology are also considered. The results are placed in the wider context of research on Scottish Gaelic terminology and corpus planning. The paper argues that the examined terminology is shaped by the dominance of English, as well as by practical concerns arising from the current language planning situation.